Pengaruh Penggunaan Media Gambar Seri terhadap Kemampuan Menulis Dongeng Fabel Siswa Sekolah Dasar Sekota Bengkulu - Anggun Saputri; Nani Yuliantini (JURIDIKDAS, 2023)
This research aims to determine the effect of the use of drawing media series on the ability to write fable fairytales students class IV elementary school Sekota Bengkulu. This type of research is a quantitative research. Reasearch Method used Quasy Experimental research with the design resarch The Matching Only Posttset Control Group Design. This research conucted after giving treatment to the sample class. The population in this research are all elementary school and students who are accredited A and used the curriculum KTSP Sekota Bengkulu. The sampling technique used the cluster random sampling.The sample in this research is students of class IVB SDN 60 as the experimental class and the students of class IVB SDN 82 as the control class. This research instrument used a description test (essay). Data analysis used is descriptive analysis, prerequisite test and inferential analysis that is t-test. T-test of both sample classes with significance level of 5%, obtained tcount = 1,74 while ttable =1,68 tcount > ttable so that H0 rejected and Ha accepted. It means that there the influence of the use of drawing media series to the ability to write fable fairytales class students IV elementary school sekota Bengkulu.